Art Education and Its Role in Reviving Popular Heritage - علي, نورا عبد الله (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
The present study, titled _Art Education and Its Role in Reviving Popular Heritage, aims to examine the significance, approaches, and challenges from the perspective of art education teachers. The researcher adopted a descriptive analytical method due to its suitability for the study procedures. The research population consisted of art education teachers in primary schools under the General Directorate of Education in Baghdad/Al-Karkh II, totaling 678 teachers. The research sample, to whom the questionnaire was distributed, included 40 art education teachers for the first semester of the academic year 2024/2025, selected through random sampling.The researcher relied on a questionnaire as the primary research tool and designed a specific instrument for this study in accordance with psychometric properties. The questionnaire consisted of 20 statements distributed across three axes: The contribution of art education in reviving popular heritage (8 statements). Approaches to developing values of popular heritage (6 statements). Challenges facing art education in the effort to revive popular heritage (6 statements). The responses were measured using a three-point scale indicating agreement levels: high, medium, and low, assigned scores of 3, 2, and 1, respectively. The researcher ensured the validity of the instrument through expert evaluation and assessed reliability using Cronbach's alpha coefficient. After completing the questionnaire development procedures, it was administered to the research sample.The researcher used the _SPSS_ software to analyze and interpret the data to derive results. The study reached several findings, including a strong agreement (92%) among the sample members on the role of art education in reviving popular heritage among primary school students. Based on the results, the study concluded that art education serves as an ideal medium for fostering positive attitudes toward popular heritage among learners, encouraging appreciation, understanding its components and aesthetic features, and preserving it from extinction.